Fabrication of polymeric scaffold via additive manufacturing - Foo, Yong Sheng (2014)
Cardiovascular disease is the number one cause of the death in the world today. The most common form of the disease is atherosclerosis which is the narrowing of the blood vessels due to the deposition of plague on the vessel walls. Treatment of the disease is dependent on its severity and often involves the prescription of drugs in minor cases and bypass surgery in severe cases. In bypass surgery, the patient’s own blood vessels is often used as the first choice, however, if the patient does not have sufficient quality blood vessels due to previous operations or injury, artificial blood vessels may be used. Although there are already artificial blood vessels available in the market made of Teflon and Dacron, they are only suitable to be used in larger diameter blood vessels. When used to replace blood vessels of smaller diameter, thrombosis (i.e. the formation of blood clot) tends to occur. Hence there is a continuous effort of scientist around the world to search for the solution to this problem through tissue engineering.